Female and male mouse lung group 2 innate lymphoid cells differ in gene expression profiles and cytokine production - Mathä, Laura (PLoS One, 2019)
Epidemiological studies have shown sex differences in prevalence of non-allergic asthma. Recent reports demonstrated negative effects of androgen signaling on group 2 innate lymphoid cells (ILC2s), explaining a potential mechanism behind sex bias in asthma prevalence. To further understand sex-related differences in ILC2 functions and ILC2 intrinsic or lung environmental mechanisms behind it, we have investigated the effects of sex and age on lung ILC2 function, the amounts of ILC2-activating cytokines in the lung and gene expression profiles of male and female ILC2s. Flow cytometric analyses of naive male and female mouse lung ILC2s showed no difference in their numbers. However, upon three daily intranasal IL-33 injections, lung ILC2s in postpubertal female mice expanded to a greater degree than male counterpart. In line with in vivo results, purified female mouse lung ILC2s produced more cytokines than male ILC2s upon in vitro stimulation. Gene expression profiles of purified naïve male and female ILC2s differed in 4% of the genes, and gene set enrichment analysis showed that female ILC2s are enriched for gene signatures of memory T cells. We did not observe similar degree of differences between female and male ILC2s after IL-33 stimulation. ILC2-activating cytokines including IL-33, IL-7 and TSLP were more highly expressed in whole lung homogenate samples prepared from naïve post pubertal female mouse lung than male mouse lung. Moreover, the differences in responsiveness of male and female ILC2s to IL-33 were not affected in IL-33-deficient mice. These results suggest that female ILC2s are more readily activated than male ILC2s due to their gene expression at the naïve state, which is potentially influenced by the lung environment.